6 Current utility of FFRCT in the United Kingdom. (May 2019) - Asher, Alex; Thornton, George; Singhal, Arvind; Davies, Ceri; Wragg, Andrew
Abstract : Background: In 2016 NICE produced Medical Technology Guidance approving the use of HeartFlow FFRCT for the investigation of patients presenting chest pain of new onset in the UK. The extent to which this technology has been adopted within the NHS in the UK is not yet known Objectives: Primarily we aimed to identify which centres in the UK are currently using CTCA with FFRCT technology and the total number of FFRCT scans compared to the total number of CTCAs in the 2016–17 financial year. Secondarily we aimed to identify which centres had capability for use of FFRCT technology in the coming years. Methods: A Freedom of Information request was submitted to all NHS trusts asking the following questions: Does the trust have a 64-slice (or above) CT scanner? Does the trust perform Coronary CT angiography? How many Coronary CT Angiography scans were performed in the financial year 2016–2017? Does your Trust have access to Coronary CT Angiography with non-invasive FFR analysis or HeartFlow FFRCT technology? If so how many FFRCT scans have been performed in the financial year 2016–2017? Results: We achieved a 99% response rate of all acute NHS trusts (159/161). 74% of all trusts reported providing a CTCA service. 70, 928 CTCA scans were reported by these trusts. 12 trusts (8%) reported having access to FFRCT technology although only half of these had performed FFRCT analysis in 2016–17. 11/12 trusts were located in England and 1/12 in Scotland. Overall 210 FFRCT scans were performed in these 6 trusts. FFRCT analysis was used in just 0.3% of all the CTCAs in the UK in 2016–17. All trusts performing FFRCT scans performed at least 600 CTCAs per year. All FFRCT scans were requested in England in this period. A further 139/161 trusts (86%) have potential to set up a future FFRCT service based on this data. Conclusion: FFRCT technology remains limited to a handful of high volume centres. Only a small number of scans are being performed nationally but there is scope for significant expansion in years to come. There is marked geographical variation in availability of FFRCT currently. Conflict of Interest: Nil